Awareness and attitude of patients' parents toward pulp therapy of the primary teeth: A clinical survey - J V Setty; I Srinivasan (Wolters Kluwer Medknow Publications, 2011)
Aims and Objective: The present study was carried out to find out the awareness and attitude of parents of patients, toward the pulpal treatment of primary teeth, visiting a dental hospital in a Bangalore suburban area. Materials and Methods: A total of 685 parents of the child patients requiring pulp treatment procedures visiting the dental OPD over a period of 18 months were personally interviewed with a questionnaire and their responses were immediately computed. Results: Urban populations seeking dental treatment are more in number as compared to the rural population. Pain and associated feature was the most common reason among both urban (71.92%) and rural (93.3%) patients visiting a dental office. Conclusions: It is important to create more awareness among the populace of our country about the significance of maintaining a healthy primary dentition and attendant sequalae if not done so.